Pendidikan Bagi Komuniti Orang Kurang Upaya Penglihatan di Malaysia: Satu Analisis daripada Perspektif Sejarah [Education of the the partially blind in Malaysia: an analyses from historical perspectives] - Wong, H.S.; Sebestian, S. (2002)
This article provides an overview of the historical educational development of persons with visual disability in Malaysia. The main discussion of this article is from the colonial period and after independence including recent development in the field. Primary education for the blind was established during the colonial period and secondary education only started after independence. Based on available review of literature, it is apparent that four key sectors have played essential roles in the educational development of persons with visual disability. They are religious organizations, local government, Ministry of Education and persons with visual disabilities themselves. This historical analysis provides the growth and development of education of the visual disabled in Malaysia. This article also provides brief information on the status of blind students’ academic progress in the University of Malaya.